(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Deaths due to poisons form inexorable part of all unnatural deaths in the current era of social,cultural and personal dilemma existing among mankind. Stress, poverty, financial insecurities, personal conflicts,unemployment, ill health, psychological disturbances, difficulties in psycho-social adaptability and lonelinesscontribute significantly to the ever-increasing mortality in poison deaths.Methods and results: A 20-month prospective descriptive study was conducted at the Department of ForensicMedicine and Toxicology, Victoria Hospital, Bangalore Medical College and Research Institute on cases ofdeath due to poisoning. Out of 110 cases, maximum number of cases were male (63.63%), in the age groupof 21-30 years (33.63%). 92.72% belonged to Hindu religion and 55.45% belonged to the upper lower class.54.54% belonged to urban areas and 60% were married victims. Maximum numbers of cases (38.18%)were recorded in winter, commonly between 5pm – 10 pm (39.09%) and 84.54% occurred at the placeof residence. 84.54% of cases were suicidal in nature with psychological causes being the most commonmotive (30.90%). 81.81% of cases received treatment and 34.53% succumbed to death within 1-7 daysof consumption of poison. Organophosphorus group of insecticide (50%) was the most common poisonencountered, followed by Phosphide ions (30%).Conclusion: Poisoning is a major epidemic of non-communicable disease in the present century. Suicidaland accidental poisoning are significant contributors to morbidity and mortality throughout the world.